A new cytotoxic diterpenoid glycoside from the leaves of Blumea lacera and its effects on apoptosis and cell cycle - Akter, Raushanara A.; Uddin, Shaikh J.; Tiralongo, Joe; Grice, Darren; Tiralongo, Evelin (© 2016 Taylor and Francis Ltd., 2016)
This article was published in Natural Product Research [© 2016 Taylor and Francis Ltd.] and the definite version is available at: https://goo.gl/ba4EOj